Tutela de urgência ambiental na ação civil pública - Alcântara, Fabio Bonomo de (2005)
This dissertation deals with the environmental protection study, as well as the techniques aiming at the celerity of the jurisdictional force. This research aims at taking care of the fair and effective environmental protection, approaching questions concerning meta-individual rights. The formidable Lei de Ação Civil Pública (Law of Public Civil Action), will also be a subject of this research, since it is the protection tool of these new rights. The importance of studying this law is obvious, because some institutions well established in the civil processual law, especially due to the continuous social evolution, go through deep and constant changes which demand new warranties for accessing justice. Lastly, it is worth emphasizing that this piece of work will be focused on the analysis of the harmful effects of time in the process, always trying to establish a priority of preventive protection, over remedial protection due to the irreversibility of environmental damages.